Emergency contraception. Issue 11 (November 2018) - Pitt, Katherine
Emergency contraception is used to prevent unwanted pregnancy in women following unprotected sexual intercourse, including contraceptive failure. The primary healthcare team has an important role in the provision of emergency contraception. Other providers include sexual health clinics, pharmacies and emergency departments. Three methods are used in the UK: levonorgestrel oral emergency contraception, ulipristal oral emergency contraception, and the copper intrauterine device. In 2017 the Faculty of Sexual and Reproductive Healthcare (FSRH) produced guidance on emergency contraception and quick starting regular contraception. This article will provide an approach to counselling patients about emergency contraception, and practice pointers from the FSRH guidelines. Case studies will be used for illustration.